Legal Counseling on Cybercrime as a Preventive Effort Against Crime at Hifdzil Quran Al-Mubarak Islamic Boarding School Jambi - Tri Imam Munandar; Hafrida Hafrida; Ansorullah Ansorullah; Nelli Herlina (Probono and Community Service Journal, 2026)
The advancement of information technology has brought significant changes in various aspects of life, including in religious-based educational environments such as Islamic boarding schools (pesantren). These institutions are not immune to such threats, considering the ease of access to the internet and digital devices. Although technology offers many benefits, its development also increases the risk of cybercrimes, including online gambling. This activity aims to provide legal understanding related to cybercrime in general and online gambling in particular, as well as to equip students (santri) with life skills and encourage their active participation in preventing and combating such crimes. The motives behind cybercrimes are generally not limited to economic factors alone but can also stem from intellectual motives. From an economic perspective, online gambling is a prevalent form of cybercrime in Jambi Province, especially among children, teenagers, and civil servants. Many students and teachers are still unaware that certain online activities can constitute crimes, including online gambling—both in terms of their legal aspects, impacts, and efforts for prevention. Jambi Province, in particular, has been identified as having one of the highest numbers of online gambling cases in Indonesia. The methods used include socialization, simulation, and interactive discussions. After participating in this legal education program, it is expected that the students will not only refrain from engaging in online gambling but also become pioneers of digital da’wah, promoting positive values and encouraging the community to lead a healthier and more Islamic lifestyle. Kemajuan teknologi informasi telah membawa perubahan signifikan dalam berbagai aspek kehidupan, termasuk di lingkungan pendidikan berbasis keagamaan seperti pesantren. Lingkungan pesantren pun tidak luput dari ancaman ini, mengingat kemudahan akses terhadap internet dan perangkat digital. Meskipun memberikan manfaat, perkembangan teknologi juga meningkatkan risiko terjadinya kejahatan siber termasuk judi online. Kegiatan ini bertujuan untuk memberikan pemahaman hukum mengenai kejahatan siber pada umumnya serta judi online khususnya. serta membekali para santri dengan lifeskill dan partisipasi aktif dalam mencegah serta menanggulangi kejahatan ini. Motif pelaku kejahatan siber pada umumnya bukannya hanya sekedar motif ekonomi semata namun juga kejahatan ini dilakukan dengan motif intelektual. Dari motif ekonomi, judi online merupakan kejahatan siber yang marak terjadi di Provinsi jambi khususnya oleh anak dan remaja serta ASN. Banyak santri dan tenaga pengajar belum memahami bahwa beberapa tindakan di internet bisa termasuk kejahatan termasuk judi online, baik itu aspek hukum, dampak serta bagaimana Upaya penanggulangannya. bahwa Provinsi Jambi khususnya merupakan Provinsi kasus judi online tertinggi di Indonesia Metode yang dilakukan berupa sosialisasi, simulasi dan tanya jawab. Perubahan literasi digital khususnya aspek hukum digital berdampak pada santri, dan juga diharapkan santri menjadi pelopor dakwah digital yang menyebarkan nilai-nilai kebaikan dan mengajak masyarakat untuk hidup lebih sehat dan Islami